Keeping the head up: lessons learned from the international debate on business and human rights - Terán, Daniel Fernando Uribe (Homa Publica - Revista Internacional de Derechos Humanos y Empresas, 2018)
The present paper analyses the negotiating history of different initiatives related to the issue of business and human rights in the United Nations. It particularly focusses on the different lessons learned in such negotiations with the view of identifying and clarifying the challenges developing countries face in the negotiation of an international instrument on business and human rights which is currently discussed in the United Nations Human Rights Council.